The Work of Painter Ivan Svyatenko in the Context of the Artistic Life of Slobozhanshchyna During the Art Nouveau Period - Sokolyuk, Oksana (HUDPROM: The Ukrainian Art and Design Journal, 2024)
The article is devoted to the work of the forgotten painter from Slobozhanshchyna Ivan Svyatenko. The information previously introduced into scientific circulation by researchers was scattered and fragmentary. Therefore, the author of this article focused primarily on systematizing the known facts and searching for new ones. As a result, it became possible to not only highlight Svyatenko’s significant role in the artistic life of Kharkiv but also to shed light on his influence in the small Slobozhanshchyna town of Lebedyn at that time. The article expands our understanding of Svyatenko’s work as a creator of both sacred and secular paintings and establishes a chronology of his artistic activity. As shown in this study, his career began in 1887, while the last identified and signed work by Svyatenko dates back to 1929. The author introduces previously unknown works by Svyatenko into scientific circulation, including murals in the physics building of the Kharkiv Technology Institute (now the National Technical University “Kharkiv Polytechnic Institute”). The date of these grisaille technique paintings has been identified, along with the portraits of prominent European physicists depicted in them, which have survived to this day – Julius Robert von Mayer and William John Macquorn Rankine. In the Cathedral of the Ascension of the Lord, built in Lebedyn in the second half of the 19th century, the author identified an icon of St. John the Theologian, as well as an icon depicting Saints Peter and Paul, both painted by Svyatenko and dated 1914. Created using gesso on wood with a gilded carved background, these icons were likely intended for the Deesis tier. Stylistic analysis revealed the artist’s inclination toward the stylization characteristic of the Art Nouveau style, which had spread throughout Europe and influenced artists of Slobozhanshchyna. The last works by Svyatenko identified by the author include portraits of Ukrainian writers Ivan Franko and Marko Vovchok, which were printed as postcards by the State Publishing House of Ukraine in the 1920s, as well as the restoration of a religious painting titled Mary Magdalene, dated 1929. Additionally, the article introduces a number of new facts that deepen our understanding of Svyatenko’s participation in the artistic life of Slobozhanshchyna. Notably, it establishes the date of his admission to the Association of Kharkiv Artists (March 15, 1906) and expands the list of his works exhibited by this association. Furthermore, an archival photograph was discovered in which Svyatenko appears alongside other members of the Association of Kharkiv Artists, dating from approximately 1907–1910.